Investigating adaptation of Staphylococcus aureus to hand sanitisers and subsequent antibiotic co-selection via experimental evolution - Seam; Alam, Shamrin Adiba (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.